PENGEMBANGAN MEDIA PEMBELAJARAN MATH TRAIN TRACK UNTUK MENGUKUR MINAT BELAJAR PESERTA DIDIK - Muhamad Azi Abdul Aziz; Farhan Maulana Muslim; Usep Kosasih; Samnur Saputra (UJMES (Uninus Journal of Mathematics Education and Science), 2023)
Mathematics is a compulsory subject at every level of school, from elementary, junior high, high school, vocational to tertiary institutions. In fact, from the results of interviews with junior high school mathematics educators, information was obtained that in general mathematics is still considered difficult to understand because mathematics is related to abstract matters, one of which is the gradient sub-material. Based on the results of field observations conducted in class VIII at one of the junior high schools in the city of Bandung, information was obtained that students really liked games. The design in this study used Formative Evaluation, with the research subjects from 20 students of Class VIII SMP students, educators, and mathematics education experts. The instrument used was the results of completing a questionnaire conducted by participants, namely class VIII students, it was found that the Math Train Track could increase students' learning interest. This research is limited only to find out the increase in students' interest in learning by the Math Train Track as a game-based learning media.